High School Students’ Motivation and Help-Seeking Strategies in English Language Learning - Fidelis Elleny Averina; Paulus Kuswandono (Yayasan Visi Intan Permata, 2022)
Motivation and help-seeking as self-regulated learning strategies are essential for the students to increase academic persistence, cope with academic challenges, and take an active role in their learning process. To date, self-regulated learning strategy and motivation in learning have been extensively studied. However, little attention and effort have been made to investigate the correlation between a motivation variable and help-seeking strategy at the Indonesian high school level. To fill the gap in the previous research, this study aimed to investigate high school students’ motivation in learning English and the extent to which it correlated with their help-seeking strategy. To reach the aforementioned aim, a correlational-method design was applied in this research. The researchers gathered the data using two types of data collection techniques, namely a close-ended questionnaire and semi-structured interview to provide triangulation. Ninety-eight students of a private senior high school in Cirebon, Indonesia were involved in this study. The findings revealed that those high school students tended to be instrumentally motivated in learning English. Furthermore, they were also reported to have positive attitudes and good initiatives to engage in help-seeking strategies whenever it was necessary. From the statistical calculation utilizing SPSS version 25, it was found that motivation and help-seeking strategy had a strong positive correlation (r=.645), which inferred that as the students had a high level of motivation; they were more inclined to engage in help-seeking strategies.